2017
DOI: 10.1080/09638288.2017.1370498
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the driving performance of drivers with and without autism spectrum disorders under complex driving conditions

Abstract: The performances of licensed drivers with autism spectrum disorders appeared to be safer in respect to car-following distance but were poorer in their response to challenging traffic situations. Driver education for individuals with autism spectrum disorders should focus on quick identification of hazards, prompt execution of responses, and effective allocation of attention to reduce lapses in driving. Implications for rehabilitation Drivers with autism spectrum disorders reported significantly more lapses dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Regarding the first two categories, no study has been identified. As for the third category (“programs”), Hielkema et al [ 74 ] studied the effectiveness of “Coping with and Caring for infants with special needs (COPCA)”, a family-focused program applied to 43 families with young children at high risk of cerebral palsy. The results related to the group that received COPCA show that the FQoL improved over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the first two categories, no study has been identified. As for the third category (“programs”), Hielkema et al [ 74 ] studied the effectiveness of “Coping with and Caring for infants with special needs (COPCA)”, a family-focused program applied to 43 families with young children at high risk of cerebral palsy. The results related to the group that received COPCA show that the FQoL improved over time.…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al, establish a connection between the holistic nature of the FQoL and the method used. To solve this problem, Brown et al, propose that one of the parents responds on behalf of the rest of the family [ 66 ], who would thus be represented by him or her [ 74 , 87 , 94 ]. However, as Giné et al, note, there is no way to ensure that this instruction of responding on behalf of the family has been followed by the family representative [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Savage et al performed secondary analysis from the National Longitudinal Transition Study-2 (NLTS2) and reported that adolescents with mild ID were at greater risk for engagement in risky behaviours (Savage and Bouck, 2017). In addition, some studies have reported poor driving performance of autistic patients in virtual settings, some of which may be due to impaired executive function in complex situations (Chee et al, 2019;Patrick et al, 2020). Epilepsy alone can also contribute to traffic accidents as the results of one Swedish nationwide cohort study (Sundelin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They also represent one of the most common injuries requiring medical attention for Aboriginal and Torres Strait Islander children < 6 years of age (Department of Social Services 2009 ; Department of Social Services 2011 ). As an injury burns are complex, resource intensive and costly, creating significant occupation and social limitations (Kornhaber et al 2017 ; Dolp et al 2018 ; Weedon and Potterton 2011 ; McGarry et al 2014 ). Depending on severity, children and their families can have extensive hospital lengths of stay (LOS) for initial treatment, as well as ongoing rehospitalisation for treatment and scar management.…”
Section: Introductionmentioning
confidence: 99%